Genital porokeratosis: A case report and review of pathogenesis and genitogluteal subtypes of porokeratosis - Camille Hamm; Jennifer Lipson (SAGE Open Medical Case Reports)
Porokeratosis is a condition characterized by abnormal epidermal keratinization with a unique morphology of papules or plaques surrounded by a thread-like border of scale corresponding to the cornoid lamella on histology. Many established subtypes have been described; however, genitogluteal porokeratosis is a rare entity. We present the case of a 58-year-old male with pruritic reddish lesions affecting the genitals and thighs, diagnosed with genital porokeratosis. This case highlights features of this rare and diagnostically challenging subtype of porokeratosis.